2022
DOI: 10.1536/ihj.21-404
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Protects Against Hypoxia-Induced Cardiomyocyte Apoptosis Through Inhibiting NLRP3/Caspase-1 Pathway <i>in vivo</i> and <i>in vitro</i>

Abstract: This study aims to explore the underlying mechanisms of how Pioglitazone (Pio) affects myocardial ischemia-reperfusion (I/R) injury. In this study, after pretreatment of Pio, the pathologic change of myocardial tissues was measured via hematoxylin and eosin staining. The release of lactate dehydrogenase (LDH), superoxide dismutase (SOD), and nitric oxide (NO) were measured. The cardiomyocyte apoptosis was detected via TUNEL assay and flow cytometry assay. The mitochondrial membrane potential (ΔΨm) was estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Of note, several publications previously suggested that pioglitazone and PPAR‐γ prevented NLRP3 inflammasome activation. Pioglitazone inhibited the expression levels of NLRP3 inflammasome components, including NLRP3, ASC, procaspase‐1, and pro‐IL‐1β in the renal cortex of apoE‐deficient mice [35] and in rat H9c2 cardiomyocyte cells upon ischemia–reperfusion stimulation [36]. Rosiglitazone, another PPAR‐γ agonist, inhibited angiotensin II‐induced NLRP3 inflammasome components in mouse C2C12 myotube cells but did not affect the basal levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, several publications previously suggested that pioglitazone and PPAR‐γ prevented NLRP3 inflammasome activation. Pioglitazone inhibited the expression levels of NLRP3 inflammasome components, including NLRP3, ASC, procaspase‐1, and pro‐IL‐1β in the renal cortex of apoE‐deficient mice [35] and in rat H9c2 cardiomyocyte cells upon ischemia–reperfusion stimulation [36]. Rosiglitazone, another PPAR‐γ agonist, inhibited angiotensin II‐induced NLRP3 inflammasome components in mouse C2C12 myotube cells but did not affect the basal levels [37].…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 inflammasome, a multiprotein binding compound consisting of NLRP3, connector protein ASC and effector protein pro-caspase-1, is activated under stress and plays an important role in cardiac fibrosis ( 69 71 ). The inflammasome exerts an inflammatory effect by regulating the release of proinflammatory cytokines including IL-1β and IL-18, contributing to cardiomyocyte apoptosis and dysfunction, and leading to ventricular remodeling and heart failure ( 69 , 72 , 73 ). NFκB is a master regulator of inflammatory gene expression and is activated in a variety of cardiac diseases, including congestive heart failure and cardiac hypertrophy ( 74 ).…”
Section: Discussionmentioning
confidence: 99%